Transdisciplinary Obesity Prevention Research Sciences (TOPRS) Curriculum Increases Knowledge About Complex Causes and Consequences of Obesity for Undergraduate Students - Barbara H. Fiese; Amber Hammons; Brenda Koester; Gabriela L. Garcia; Loran Parker; Dorothy Teegarden (Frontiers Media S.A., 2019)
Most researchers and public health officials would agree that the causes and consequences of obesity are complex and multi-faceted. However, curricula designed to address these complexities are limited and often guided by a single discipline. The purpose of the Transdisciplinary Obesity Prevention Research Sciences (TOPRS) program was to develop a "flip-the-classroom" curriculum on obesity prevention across multiple disciplines such that students would gain an appreciation of the complex origins of obesity. The curriculum is based on the 6 C's model (cell, child, clan, community, country, culture) that proposes a cell-to-society approach to obesity. Twenty video micro-lectures were developed and students were tested on content knowledge pre- and post-viewing. The curriculum was administered at three university sites to 74 undergraduate students across 23 declared majors from 2014-2016. There were significant gains in knowledge about the causes and consequences of obesity. Recommendations are offered to adopt this curriculum in undergraduate and other educational settings.